Efficacy of combined chamomile aromatherapy and LI-4 (hegu) acupressure on post-cesarean pain: A quasi-experimental study - Rahmah Widyaningrum; An Nisaa Ananda Subekti; Tri Hardi Miftahul Ulum (Nurse Point: Journal of Nursing, 2026)
Background: Effective pain management within the first 24 hours post-cesarean section is essential for maternal recovery. Non-pharmacological approaches, such as chamomile aromatherapy and LI-4 (Hegu) acupressure, offer accessible analgesic benefits with minimal side effects. However, evidence regarding their combined efficacy in post-cesarean patients remains limited. Purpose: This study aims to determine the effectiveness of combined chamomile aromatherapy and LI-4 acupressure in reducing pain intensity among post-cesarean women. Methods: A quasi-experimental two-group pretest–posttest design was utilized. Twenty participants were recruited via accidental sampling and allocated into an intervention group (n=10) receiving the combined therapy, and a control group (n=10) receiving deep breathing relaxation. Data normality was tested using the Kolmogorov–Smirnov test. Data were analyzed using a paired t-test for the normally distributed intervention group and a Wilcoxon test for the non-normally distributed control group. Results: Most respondents were aged 25–37 years (80% intervention; 60% control) and underwent elective cesarean sections (90% intervention; 70% control). In the intervention group, the paired t-test revealed p-values of 0.009, 0.104, and 0.081 at 4, 8, and 12 hours post-surgery, respectively. Conversely, the control group showed significant pain reduction at 4 and 8 hours (p=0.016 and p=0.034). Conclusion and recommendation: The combination of chamomile aromatherapy and LI-4 acupressure demonstrates a significant effect in reducing post-cesarean pain intensity at 4 hours post-surgery, offering a viable non-pharmacological pain management intervention.